BEBERAPA HIPOTESIS PERTUMBUHAN PEKERJAAN OFF-FARM - Hans-Dieter Evers (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1994)
Off-farm employment and non-agriculture activities have grown rapidly in the rural areas of Java due mainly to the increasing number of female workers employed in small-scale trade. Based on a through discussion on various definitions and hypotheses on the growths of trade and off-farm employment, it could be assumed that the growth of the small-scale traders does not signify that some stagnation of economy or an agricultural involution would take place, but that there will be a significant step in the transformation process on the part of the Javanese farming community as well as on the future economic development.